2014
DOI: 10.2133/dmpk.dmpk-13-rg-118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potency of Telaprevir and Its Metabolites as Inhibitors of Renal Organic Cation Transporters, a Potential Mechanism for the Elevation of Serum Creatinine

Abstract: Telaprevir-based triple therapy is a highly effective treatment for chronic hepatitis C. However, adverse reactions include reversible and dose-dependent elevation of serum creatinine levels. We speculated that this effect reflects inhibition of the renal organic cation transporters hOCT2, hMATE1, and hMATE2-K by telaprevir or its metabolites (VRT-127394 and VRT-0922061). Telaprevir, VRT-127394, and VRT-0922061 showed negligible or weak effects on hOCT2 at concentrations of ≥20 µM, but inhibited hMATE1 by 35, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…However, Nakada et al . revealed that TVR did not inhibit OCT2 at clinically relevant concentrations . This result is not consistent with those reported by Kunze et al .…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…However, Nakada et al . revealed that TVR did not inhibit OCT2 at clinically relevant concentrations . This result is not consistent with those reported by Kunze et al .…”
Section: Discussioncontrasting
confidence: 86%
“…MATE is also considered to mediate directional transport of creatinine across proximal tubules. 17,18 These studies indicate that TVR inhibits OCT2 and MATE, leading to a decrease in tubular secretion of creatinine and therefore an increase in the SCr concentration. However, Nakada et al revealed that TVR did not inhibit OCT2 at clinically relevant concentrations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, Nakada et al concluded that elevated serum creatinine during telaprevir therapy may not be related to the direct inhibition of renal organic cation transporters. 17 In addition, increase of creatinine levels was not reported in clinical trials of telaprevir. Loustaud-Ratti et al suggested that unpredictable renal toxicity might occur during therapy in addition to OCT2 inhibition.…”
Section: Discussionmentioning
confidence: 99%